(untitled) - Lane, Christel; Christel Lane; Reinhard Bachmann (New York, 1998)
This original book is the first to offer a wide-ranging study of trust within and between organizations from the perspective of several social and management sciences. The specially commissioned contributions, many from well-known experts combine theoretical analysis of problems around trust with empirical study in a range of different organizations in contexts such as China, Japan, India, the US, as well as several European countries. The wide theoretical scope, together with the range of organizational settings and the rich empirical detail of behavior around trust and opportunism, make this an important and instructive volume
Keywords: Organizational behavior; Trust; Corporate culture